Time series analysis of heavy metal concentrations along the watershed gradient in Cameron Highlands: geospatial approaches - Haron, Siti Humaira; Sahid, Ismail; Mispan, Muhammad Radzali; Abd Rahman, Nor Faiza; Khalid, Khairi; Abdul Rasid, Muhammad Zamir; Mohd Sidek, Lariyah (IOP Publishing, 2016)
Heavy metal, particularly cadmium, lead, and arsenic, constitute a significant potential threat to human health. Some metals are extremely toxic to humans and the toxic heavy metals of greatest concern include cadmium, lead, and arsenic. The objective of the study conducted was to determine the accumulation and distribution status of heavy metal cadmium (Cd) in the sediment of Bertam River from September 2014 to February 2015 in the agricultural areas of Cameron Highlands, Malaysia. The sediment samples were collected randomly in three replicates from ten sampling points in the agricultural areas of Cameron Highlands. The heavy metals in the sediment were extracted using the wet acid method and the sample concentrations are then tested for metal concentrations by the spectrography method using Inductively Coupled Plasma (ICP) spectrography. Inverse distance weighting (IDW) was used to create a map of metal concentrations for a point on the polygon dataset spatial interpolation. There is an increasing trend of Cd from the upstream to downstream stations along Bertam River during the rainy season. The activity range of Cd is 0.07 to 2.83 µg/g during the rainy season, whereas, during the dry season, Cd activity ranged from 0.26-0.83µg/g.